Universal Early Childhood Education and Adolescent Risky Behavior - Michihito Ando; Hiroaki Mori; Shintaro Yamaguchi (Institute of Labor Economics (IZA), 2022)
The evidence for the effects of early childhood education on risky behavior in adolescence is limited. This paper studies the consequences of a reform of a large-scale universal kindergarten program in Japan. Exploiting a staggered expansion of kindergartens across regions, we estimate the effects of the reform using an event study model. Our estimates indicate that the reform significantly reduced juvenile violent arrests and the rate of teenage pregnancy, but we do not find that the reform increased the high school enrollment rate. We suspect that improved non-cognitive skills can account for the reduction of risky behavior in adolescence.
Keywords: 330; early childhood education; crime; teenage pregnancy